What specific exercise training is most effective exercise training method for patients on maintenance hemodialysis with sarcopenia: a network meta-analysis - Li, Ying; Li, Jingjing; Chen, Xiaoan; Shi, Yuegong; Shen, Jie; Huang, Ting (Frontiers in Nutrition, 2024)
Objective: The present study aimed to investigate the influence of different exercise methods on sarcopenia patients receiving maintenance hemodialysis (MHD) by conducting a network meta-analysis.: The PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure (CNKI), and Wanfang databases were searched online for relevant articles published until May 2024. Based on the inclusion and exclusion criteria, we selected 10 articles that compared the effects of 7 exercise interventions on sarcopenia patients receiving MHD. Results: The results of network meta-analysis showed that resistance training (RT) (standardized mean difference (SMD)= 4.54; 95% confidence interval( CI): 3.27~5.80) significantly improved the handgrip strength (HGS) of sarcopenia patients receiving MHD as compared to Baduanjin exercise (BAE) (SMD = 4.19; 95% CI: 2.31~6.07), bicycle exercise (BIE) (SMD = 4.06; 95% CI: 0.02~8.10), and combined movement (CE) (SMD = 3.50; 95% CI: 3.13~3.87). Compared to normal care (NC), BAE (SMD = 0.15; 95% CI: 0.07~0.23), RT (SMD = 0.34; 95% CI: 0.06~0.62), and CE (SMD = 0.37; 95% CI: 0.16~0.58) significantly improved skeletal muscle mass index (SMI) in sarcopenia patients receiving MHD. Conclusion: This study showed that RT has a positive effect on improving HGS in sarcopenia patients receiving MHD. CE also showed good results in enhancing SMI in MHD patients with sarcopenia. More randomized controlled trials are required to better understand the effectiveness of these exercise interventions and the potential underlying mechanisms.